1978
DOI: 10.1016/s0022-5347(17)57394-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Staging of Prostatic Carcinoma: Three Years of Experience

Abstract: The immunological specificity of prostatic acid phosphatase has been demonstrated previously in the laboratory and used in a small number of patients. Our findings in 96 patients using gel immunodiffusion with an acid phosphatase antiserum in the study of bone marrow aspirates and lymph nodes are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1983
1983

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, a small fraction is immunologically cross-reactive, and it is possible that the reported tumor originated from a pancreatic cell clone which secreted this cross-reactive AP. Drucker and Moncure (1978) reported cross-reactivity of bone marrow AP in a 57-year-old woman with chronic granulocytic leukemia. Pontes et a1 (1 978) described a patient with lung carcinoma who had cross-reactive bone marrow AP.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, a small fraction is immunologically cross-reactive, and it is possible that the reported tumor originated from a pancreatic cell clone which secreted this cross-reactive AP. Drucker and Moncure (1978) reported cross-reactivity of bone marrow AP in a 57-year-old woman with chronic granulocytic leukemia. Pontes et a1 (1 978) described a patient with lung carcinoma who had cross-reactive bone marrow AP.…”
Section: Discussionmentioning
confidence: 98%
“…Thus bone marrow RGID may be a more useful indicator of prostatic carcinoma metastatic to bone than conventional techniques. Moncure (1978) has reported the identification of PAP in tissue samples other than bone marrow. The present study confirms its clinical relevance in the management of all four cases reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation